Pregnancy after Cancer Treatment and Pregnancy Associated Cancer: A Single Center Experience with 96 Cases - Mert Turğal; Kemal Beksaç; Derman Başaran; Aslıhan Yazıcıoğlu; Özgür Özyüncü; Ömer Aran; M. Sinan Beksaç (Gynecology Obstetrics & Reproductive Medicine, 2015)
OBJECTIVE: The objective of our study was to evaluate our experience on pregnancies after cancer treatment and pregnancy-associated cancer.